2002
DOI: 10.1097/01.asn.0000028642.26222.00
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Membrane Expression of Proteinase 3 (PR3) Is Related to Relapse in PR3-ANCA-Associated Vasculitis

Abstract: Abstract. Wegener granulomatosis (WG) is strongly associated with the presence of antineutrophil cytoplasm autoantibodies (ANCA) with specificity for proteinase 3 (PR3). Relapses of WG are frequently preceded by a rise of autoantibody titer and PR3-ANCA are able to activate primed neutrophils in vitro. Except being stored intracellularly and translocated to the cell surface upon neutrophil stimulation, PR3 can also be detected on the surface of non-stimulated neutrophils (membrane PR3 or mPR3), with an interin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
124
0
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 20 publications
11
124
0
9
Order By: Relevance
“…This finding has not yet been reported. These data extend those of an earlier report (15). Because mPR3 expression seems pivotal and genetically determined, we next differentiated human CD34 ϩ progenitor cells to neutrophils.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This finding has not yet been reported. These data extend those of an earlier report (15). Because mPR3 expression seems pivotal and genetically determined, we next differentiated human CD34 ϩ progenitor cells to neutrophils.…”
Section: Discussionsupporting
confidence: 87%
“…On the basis of this mPR3 expression pattern, neutrophils can be divided into an mPR3 high and an mPR3 low subset. This bimodal expression pattern is stable in a given individual, does not change with cell activation, and is genetically determined (15)(16)(17). Other investigators and our own group demonstrated that a large percentage of mPR3 high neutrophils provides a risk factor for WG (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This association was limited to the GPA and PR3‐ANCA subsets (Table 2), consistent with the pathophysiologic relevance of the PRTN3 ‐encoded PR3 serine protease to these phenotypes 17.…”
Section: Resultssupporting
confidence: 75%